Acute myocardial infarction after a wasp sting. Issue 4 (April 1988) - Jones, E; Joy, M
Abstract : A 56 year old man with ischaemic heart disease and known allergy to wasp venom was stung in the mouth by a wasp and within four hours sustained an acute myocardial infarction. This complication has been described on only three previous occasions. Possible pathogenic mechanisms include the anaphylactic reaction itself, the action of wasp venom constituents, and therapeutic intervention with adrenaline.